2022
DOI: 10.1111/1759-7714.14614
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and oncological outcomes of video‐assisted thoracic surgery versus thoracotomy for pathologic N2 disease in non–small cell lung cancer: A comprehensive systematic review and meta‐analysis

Abstract: This meta-analysis aimed to evaluate the feasibility and oncological outcomes between video-assisted thoracic surgery (VATS) and thoracotomy for non-small cell lung cancer (NSCLC) patients with pathologic N2 (pN2) disease. Data for analysis included shortterm outcomes and long-term outcomes. We calculated the weighted mean differences (WMDs) for continuous data and the results of overall survival (OS) and disease free survival (DFS) were pooled using the hazard ratios (HRs) with 95% confidence intervals (CIs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…VATS is a thoracic surgical technique that is less invasive, less painful, and has a faster recovery than the traditional sternotomy, and has become the preferred treatment for non‐small cell lung cancer 7 . Most recent clinical studies have reported that VATS for early‐stage lung cancer can shorten operative time, reduce intraoperative bleeding and perioperative pain, and reduce inflammation and complications, with significant clinical efficacy compared with traditional open‐heart surgery 8‐12 . There are many clinical reports on VATS for lung cancer; however, while surgical site wound infections are among the most common postoperative complications in patients undergoing surgery, there are few studies on the effects of VATS on postoperative wound infection and wound pain in patients with lung cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…VATS is a thoracic surgical technique that is less invasive, less painful, and has a faster recovery than the traditional sternotomy, and has become the preferred treatment for non‐small cell lung cancer 7 . Most recent clinical studies have reported that VATS for early‐stage lung cancer can shorten operative time, reduce intraoperative bleeding and perioperative pain, and reduce inflammation and complications, with significant clinical efficacy compared with traditional open‐heart surgery 8‐12 . There are many clinical reports on VATS for lung cancer; however, while surgical site wound infections are among the most common postoperative complications in patients undergoing surgery, there are few studies on the effects of VATS on postoperative wound infection and wound pain in patients with lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…7 Most recent clinical studies have reported that VATS for early-stage lung cancer can shorten operative time, reduce intraoperative bleeding and perioperative pain, and reduce inflammation and complications, with significant clinical efficacy compared with traditional open-heart surgery. [8][9][10][11][12] There are many clinical reports on VATS for lung cancer; however, while surgical site wound infections are among the most common postoperative complications in patients undergoing surgery, there are few studies on the effects of VATS on postoperative wound infection and wound pain in patients with lung cancer. The aim of this study was to investigate the effect of VATS on surgical site wound infection and wound pain in patients with lung cancer, with the hope of facilitating evidence-based decision-making for optimal surgical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the thoracotomy, thoracoscopic has a lot of benefits in terms of less complications after operation and shorter stay in the hospital 18–20 . Furthermore, it can decrease surgical time and decrease haemorrhage during operation than conventional thoracotomy for early stage lung cancer 21–25 . The purpose of this research is to evaluate the efficacy of thoracoscopic surgery in comparison with that of thoracotomy.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Furthermore, it can decrease surgical time and decrease haemorrhage during operation than conventional thoracotomy for early stage lung cancer. [21][22][23][24][25] The purpose of this research is to evaluate the efficacy of thoracoscopic surgery in comparison with that of thoracotomy.…”
Section: Introductionmentioning
confidence: 99%
“…After neoadjuvant therapy for N2 NSCLC, the tumor and mediastinal nodal stations may appear inflamed and have dense adhesions, which increase the risk of surgery ( 30 , 31 ). Recently, a meta-analysis only analyzed the approach VATS and OT, which ignored the RATS approach ( 32 ). Therefore, we conducted a systematic review and meta-analysis to compare the effectiveness and safety of MIS and OT for N2 NSCLC.…”
Section: Introductionmentioning
confidence: 99%